PENGARUH RASIO LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dewanto, Alfret Kristanto (Fakultas Ekonomi Universitas Tadulako, 2017)
Sample in study consists of 11 companies that were selected by purposive sampling method. Data collecting technique is documentary analysis using the data of annual reports of food and beverage companies listed on Indonesia Stock Exchange in 2010 ? 2014. Method of data analysis uses panel data and multiple linear regressions with software Eviews version 7. The results show that six independent variables studied simultaneously influence the company value with sig. probability 0.000011 and F-count <0.05. The t-tests indicate that the Times Interest Earned Ratio, Long term- Debt to Equity Ratio, ROA, NPM and ROE have no significant influence on the company value: X2 = 0.2845, X3 = 0.1626, X4 = 0.0576, 0.2678 = X5, X6 = 0.6344, 0.05 ? ?. Debt Ratio has significantinfluence on company value, with the value X1 = 0.0192 ? 0.05. R2 value is 0.483863 and simultaneously, six independent variables studied influence the dependent variable (the value of the company) of 48.38%, while the remaining 51.62% influenced by other variables that are not studied.